Emotional states of a character in I Smile Back movie - R.R. Okky Luthfiana; Ary Iswanto Wibowo; Yanti Rosalinah (Mitra Palupi, 2021)
Background: Depression and anxiety are complex emotional states in which cognitive evaluations and affective and physiological responses are involved. However, Laney the main character in the movie really made the audience feel emotional when watching. Purpose: The purpose of this study is to analyze the types and symptoms of depression and anxiety. Design and methods: In conducting this analysis, the study uses a qualitative description method which means the technique of collecting data or theory from books or journals obtained from internet media sources and analyzing important notes that have been made, and watching movies. Results: This study shows that depression and anxiety are described as a disease that can be experienced by anyone, as a result of the analysis found three types of depression and anxiety and seven symptoms of depression and anxiety in Laney's character, and Laney's illness due to past trauma.